Platinum-based Cancer Chemotherapeutics: Recent Trends and Future Perspectives - Parveen, Shazia (Current Chinese Science, 2022)
Platinum-based drugs have been proved to be one of the prevalent successes in the field of inorganic medicinal chemistry. So far, three generations of platinum-based drugs are on the market and are recognized to play critical roles in the treatment of various types of tumors. The most commonly used anticancer chemotherapeutics worldwide are cisplatin, oxaliplatin, and carboplatin. They are known to exhibit prominent and interesting chemo-therapeutic effects. Nevertheless, Pt chemotherapy can be limited in transformative clinical implementation owing to the severe side effects triggered by off-target activity and lowered efficacy because of acquired/intrinsic resistance in some cancer types. Incidentally, monofunctional Pt complexes, those bearing one labile ligand, initially studied in the late 1980s, are again enticing renewed attention. In comparison to the bifunctional anticancer complex bearing two labile ligands, viz., cisplatin (which creates a distortion in the DNA strands by forming inter-and intrastrand crosslinks), monofunctional Pt(II) complexes were found to exclusively bind to DNA via a solo coordination site revealed by the one leaving chloride group. However, to date, no other non-platinum metal-based anticancer drug has been able to efficaciously pass all stages of clinical trials. Hence, the hunt for novel Pt-based anticancer drugs is being pursued vigorously for the reason that they still play a principal role in the chemotherapeutic profiles of almost 50% of all cancer patients. Meanwhile, the major significant goal in the search for new Pt chemotherapeutic drugs is to focus on the following: a) exploiting their potential, b) averting the undesirable side effects, c) curing resistant tumors, and d) refining the cellular pharmacokinetic regimes. This mini-review highlights the numerous continuing efforts to produce the next generation of Pt anticancer drugs.
Keywords: anticancer activity